Symposium 8: Flourish: the eCPD Project: Supporting the integration of eportfolios for continuing professional development - Howard, James; Chesney, Sarah (Proceedings of the International Conference on Networked Learning, 2008)
Recent years have seen an increased focus on the use of eportfolios within Higher Education to aid student progression and achievement. However, the potential benefits of eportfolios as a tool to augment the continuing personal and professional development of staff remain an under researched area. The University of Cumbria's JISC funded Flourish project aims to partly address this imbalance by initiating the wide-scale implementation of eportfolios into the existing working routines of academic, service and administrative personnel. This approach rests on the belief that eportfolios will present tangible enhancements to such processes. By providing a central 'personal space' where resources and experiences can be collated, stored and reflected upon, the professional development of staff is linked to a defined, cohesive structure. As the related applications become routine and familiar, structured development may more readily become integrated into existing practices. Furthermore, as staff levels of comfort with the software increase, they are perhaps better equipped to support students in their use of eportfolios. At the heart of the Flourish project is a focus on the training and support structures required to support the sustainable integration of an eportfolio within the context of an institution undergoing significant transition. In response, the project team have developed a series of support and training mechanisms that are aligned with a rolling process of research and evaluation. The aim of this iterative approach is to critically assess the relative impact of each form of support as it is trialled, in order to further understand the integration process and inform future patterns of support. This paper reports on the delivery of a key element of the support strategy developed, a two-day 'e-learning retreat', assessing its impact as an original approach to supporting deep integration of the eportfolio software. Building on qualitative data gathered during the retreat and in the weeks following the event, four analytical themes have been identified: The need to provide the time and support structures required for engagement with the eportfolio software The benefits of team Vs individual development when integrating eportfolios into existing work practices The challenge of separating the professional from the concerns of their profession during staff development The necessity to continue the momentum of integration once back in everyday working contexts. Evidence suggests that the retreat successfully addressed challenges associated with the introduction of new technologies. However, issues remain in relation to the long-term integration of eportfolios that will inform future iterations of the support put in place. These centre on the need for a defined focus and outcome to the retreat activities and a reconsideration of the membership of the teams invited to attend.